Adenovirus-vectored immunocontraception in rat model - Lo, Sewn Cen (2012)
The rat is an invasive threat to human health, agriculture and environment. Current control methods such as trapping, poisoning and by biological means are less than satisfactory to bring the growing population under control. As such, reproductive control by immunocontraceptive technique would be a more effective method for pest management. Immunocontraceptive vaccine prevents conception by stimulating the production of antibodies that bioneutralize gamete or hormone antigen and block to fertility. Conventional booster vaccine requires recapturing of the target animal and not practical in wild. Therefore, a virus-vectored immunocontraceptive vaccine is an alternative delivery system for wild pest population control. Virus-based immunocontraceptive vaccine offers several advantages that enable natural self spreading through the pest population which is suitable for pest with high population densities and high reproductive potential. The critical involvement of the female gamete protein zona pellucida 3 (ZP3) in the fertilization process has been well documented. Therefore, an adenovirus (Ad) vector encoding rat ZP3 (rZP3) protein has been constructed. Briefly, rZP3 gene was first cloned into the shuttle vector, pSCMV (pSCMV-rZP3) followed by subsequent cloning into Ad vector (rec pAd-rZP3). Restriction enzyme analysis and PCR detection gave a distinct 1.3 kb rZP3 band. The rec pAd-rZP3 was then further transfected into the human embryonic kidney (HEK-293A) complementary cell to produce infectious replication-defective recombinant adenovirus-rZP3 (rec Ad-rZP3). Transfected HEK-293A cells showed cytopathic effect (CPE) at 12 days post infection (p.i). It was then followed by in vitro and in vivo protein expression assessment. The in vitro expression of rZP3 gene produced was screened for the presence of rZP3 gene and gene expression using PCR and reverse transcriptase PCR (RT-PCR) that gave a distinct 1.3 kbp band. The expression of rZP3 was further confirmed by SDS-PAGE and western blot analysis. High-leveled expression of rZP3 was achieved which gave an ~75kDa protein band. Furthermore, immunofluorescence staining of HEK-293A cells infected with rec Ad-rZP3 emitted strong fluorescence at the nucleus of the cells. This showed that the rZP3 gene is being expressed in vitro. The efficacy of the rec Ad-rZP3 construct was evaluated in rat model. Vaccination of laboratory rats with rec Ad-rZP3 resulted in reduction of fertility up to 30%, although statistically still below significant level (ρ>0.05). Histological examination of the treated rats demonstrated a normal follicular development. ELISA results showed that rats treated with rec Ad-rZP3 raised low anti-rZP3 antibody titers. Rat ZP3 protein was successfully expressed in vitro and in vivo. Immunization with rec Ad-rZP3 has shown incomplete suppression of fertility in the target. This may due to the vector triggering strong innate immunity which leads to the elicitation of humoral and cellular immune response that results in suppression of rZP3 protein expression. Another reason may be due to the low antibody titers produced, as it has been demonstrated that high titer of antibody was directly associated with the ability to induce infertility. As infertility is associated with ZP3 antibodies, enhancing the antibody response of rec Ad-rZP3 construct would be beneficial. However, this study serves as an important platform to transfer the rZP3 gene into a host specific viral immunocontraceptive vaccine delivery vector such as rat cytomegalovirus (RCMV).